Sulfur isotope engineering of exciton and lattice dynamics in MoS2 monolayers. (1st April 2023) - Varade, Vaibhav; Haider, Golam; Pirker, Luka; Panda, Jaganandha; Sykora, Jan; Frank, Otakar; Kalbac, Martin; Vejpravova, Jana
Abstract: The optoelectronic properties of two-dimensional (2D) atomically thin transition metal dichalcogenides (TMDCs) are predominantly governed by excitons and their interaction with lattice and various physical fields. Therefore, it is essential to understand the role played by excitons in the light–matter interaction processes. We introduce sulfur isotope engineering for the first time in the TMDC family, which enables us to disentangle the crucial role played by phonons in the optoelectronic properties of TMDCs. With the gradual introduction of heavier isotopes in chemical vapor deposition growth M o S 2, we discovered a systematic variation of lattice phonon energy. Consequently, the transient and steady-state spontaneous photoluminescence spectra were dramatically altered. Accordingly, the isotopically pure monolayers (MLs) show more intrinsic properties with enhanced emission efficiencies than isotopically mixed M o S 2 MLs. The variation of the free exciton energies with temperature for the isotopically modified M o S 2 MLs can be well described by Varshini's equation. Along with the enormous significance for practical applications, our study provides a unique platform to understand the fundamentals of optical processes in 2D systems, where the lattice-related quasi-particles play a dominant role.